TRANSPIRATION OF TRAUMA AMONG CHILDREN AND ITS RAMIFICATIONS ON THEIR COGNITIVE DEVELOPMENT - Dr. Amrik Singh, Parvanshi Sharma , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The paper discovers that trauma supervenes in young children and it affects the lives of its victims afterwards. There are several traumatic factors such as rape, public humiliation, police interrogation, racial discrimination, loss of family members, friends and property etc. that can cause trauma. It has been found that due to trauma, children experience innumerable psychic corollaries such as awful perception of death, initiation of sobs, submissiveness, abusive language, loss of sleep, hunger and self-respect, psychical tiredness, numbness, visualization of countless dead bodies in dreams, fright, hysteria, addiction to alcohol, disinterest in music, ennui for liaison, loss of temper, grubby outlook, loss of consciousness, feeling of anxiety, uncertainty, and suicidal tendencies. Furthermore, it is observed that there has been very little critical research on traum a anent cognitive development to ameliorate the mental and physical condition of the affected children. There have been a lot of interventions that target psychological trauma, but they are not sufficient to meet the developmental needs of children. There is still a paramount need to provide safe environments; support children and caregivers to understand the links between traumatic experiences and cognitive difficulties; develop positive relationships among children, parents, and caregivers; offer the targeted trauma-specific interventions to the affected children; maintain the interventions throughout childhood and adolescence; and to ensure that the developmental issues and difficulties are addressed properly.